Climate change and its impact on health: a global collaborative learning model - Okatch, Harriet; Remshifski, Patricia A.; Fennessey, Anita; Campbell, Haley; Barnoy, Sivia; Friedman, Jason; Kern, Stephen B.; Frasso, Rosemary; Sorensen, Cecilia; Bar-Shalita, Tami; Hunter, Louis N. (Frontiers in Medicine, 2024)
To address the health effects of climate change, leaders in healthcare have called for action to integrate climate adaptation and mitigation into training programs for health professionals. However, current educators may not possess sufficient climate literacy and the expertise to effectively include such content in their respective healthcare curricula. We, an international and interprofessional partnership, collaborated with experts to develop and deploy curriculum to increase health educators’ and graduate health profession students’ knowledge and competencies on climate change. In a tri-step process, the first phase included recruiting interested faculty members from two institutions and varying health professions. In phase two, faculty members collaborated to develop a faculty symposium on climate change including educational competencies required of health professions, practice standards, guidelines, and profession-specific content. Symposium outcomes included broader faculty member interest and commitment to create an interprofessional climate change course for healthcare graduate students. In phase three, course development resulted from collaboration between faculty members at the two institutions and faculty members from the Global Consortium on Climate and Health Education (GCCHE), with course objectives informed by GCCHE competencies. Climate experts and faculty members delivered the course content over a 10-week period to 30 faculty members and students representing seven health professions, who were surveyed (n = 13) for feedback. This course can serve as an example for international collaborators interested in developing climate change courses for health profession students. Lessons learned in this process include: climate change novice faculty members can develop impactful climate change courses; students and faculty members can be co-learners; diverse representation in course attendees enriches the learning experience; and collaboration is key.